IMPLEMENTATION OF BEST PRACTICES IN PROVIDING SOCIAL SERVICES IN KHARKIV REGION - Klimushyn P.S.; Lytviak O.M. (Pressing Problems of Public Administration, 2018)
The paper explores introduction of innovative services into the practice of providing social servicessuch as: automated information management system, queue management system, informationterminals, website of the social services center, personal cabinet of the user, single contact center,video surveillance system.